Decrease in Mexico's life expectancy due to multiple homicides: the murder of women adjacent to the homicide of one or more men - Rosalba Jasso Vargas (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
The objective is to analyze the effect of multiple homicides on male and female life expectancy and to provide empirical evidence of the temporal and spatial associations between male and female homicide rates by age group during the period 2002-2020. Using data from the National Institute of Statistics and Geography (INEGI) and population projections from the National Population Council (CONAPO), mortality rates due to homicide from 2002-2020 were estimated for both men and women, and the adjacency of homicides of men and women was analyzed, along with the spatial proximity between multiple homicides of men and women, along with changes in life expectancy due to homicide. Individual homicides have caused the greatest decrease in life expectancy for both men and women. The negative impact of multiple homicides on both female and male life expectancy began to draw attention in 2008. By analyzing the murders of women adjacent to the homicides of one or more men questions are raised about whether these crimes are primarily the result of criminal violence, and to a lesser extent the role of gender.